Co-Occurrence of Familial Non-Medullary Thyroid Cancer (FNMTC) and Hereditary Non-Polyposis Colorectal Cancer (HNPCC) Associated Tumors—A Cohort Study - Aswath, Kshama; Welch, James; Gubbi, Sriram; Veeraraghavan, Padmasree; Avadhanula, Shirisha; Gara, Sudheer Kumar; Dikoglu, Esra; Merino, Maria; Raffeld, Mark; Xi, Liqiang; Kebebew, Electron; Klubo-Gwiezdzinska, Joanna (Frontiers in Endocrinology, 2021)
Familial non-medullary thyroid cancer (FNMTC) is a form of endocrine malignancy exhibiting an autosomal dominant mode of inheritance with largely unknown germline molecular mechanism. Hereditary Nonpolyposis Colorectal Cancer Syndrome-(HNPCC) is another hereditary autosomal dominant cancer syndrome which, if proven to be caused by germline mutations in mismatch repair genes (MMR), is called Lynch syndrome (LS). LS results in hereditary predisposition to a number of cancers, especially colorectal and endometrial cancers with tumors characterized by microsatellite instability (MSI) and/or loss of MMR protein expression in immunohistochemistry (IHC). MSI although a rare event in thyroid cancer (TC), is known to occur in up to 2.5% of sporadic follicular TC cases. There is limited data on the role of germline MMR variants in FNMTC. The goal of this study was to analyze the potential clinical and molecular association between HNPCC and FNMTC. We performed a cohort study analyzing the demographic, clinical, and pathologic data of 43 kindreds with FNMTC and performed high-throughput whole exome sequencing (WES) of peripheral-blood DNA samples of 168 participants (54 affected by FNMTC and 140 unaffected). Family history screening revealed one Caucasian family meeting the clinical criteria for FNMTC and HNPCC. A heterozygous missense variant in the MSH2 gene c.2120G>A (p.Cys707Tyr) was detected exclusively in these kindred. This variant is predicted to be damaging/pathogenic in 17/20 in-silico models. However, immunostaining performed on the thyroid tumor tissue of two FNMTC affected members revealed intact nuclear expression of MSH2, and microsatellite stable status in both tumors. Although this MSH2 variant is rare with a minor allele frequency (MAF) of 0.00006 in Caucasians; it is more common in the South Asian population at MAF 0.003. Therefore, the MSH2 variant observed in this family is unlikely to be an etiologic factor of thyroid cancer and a common genetic association between FNMTC and HNPCC has not yet been identified. This is the first report known to us on the co-occurrence of FNMTC and HNPCC and although presented in a single family in our large FNMTC cohort, a common genetic background between the two comorbidities could not be established.